2005
DOI: 10.1007/s00213-005-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine/naloxone reduces the reinforcing and subjective effects of heroin in heroin-dependent volunteers

Abstract: These data demonstrate that both 8/2 and 32/8 mg buprenorphine/naloxone were well tolerated and effective in reducing the reinforcing and subjective effects of heroin, relative to the 2/0.5-mg dose. The data also show for the first time in humans that it is possible to quantify the efficacy and affinity of heroin for mu opioid receptors, and that 80-90% of mu receptors need to be inactivated in order to obtain significant reductions in heroin-induced effects. These results have important implications for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 38 publications
8
61
0
Order By: Relevance
“…These data are consistent with the conclusion that naloxone and buprenorphine antagonize the reinforcing effects of heroin. These results are also consistent with the finding that maintenance on the opiate antagonist naltrexone or on buprenorphine decreases heroin versus money choice in detoxified heroin-dependent humans (Mello et al, 1981(Mello et al, , 1982Comer et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…These data are consistent with the conclusion that naloxone and buprenorphine antagonize the reinforcing effects of heroin. These results are also consistent with the finding that maintenance on the opiate antagonist naltrexone or on buprenorphine decreases heroin versus money choice in detoxified heroin-dependent humans (Mello et al, 1981(Mello et al, , 1982Comer et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…than placebo, demonstrating abuse potential by the i.v. route of administration for this group (Comer et al 2002a(Comer et al , 2005(Comer et al , 2008bComer and Collins 2002). These latter findings are generally consistent with the results obtained in self-administration studies with animals and appear to be borne out by international epidemiological evidence of i.v.…”
Section: Human Laboratorysupporting
confidence: 89%
“…A laboratory comparison of a range of buprenorphine/ naloxone doses combinations on intranasal heroin selfadministration (12.5 to 50 mg) by opioid-dependent volunteers demonstrated that 8/2 mg and 32/8 mg buprenorphine/naloxone combinations were well tolerated and decreased heroin's reinforcing and subjective effects compared to a low dose of buprenorphine/naloxone (2/0.5 mg; Comer et al 2005). Thus, the combination appears to be efficacious at sufficient dose levels.…”
Section: Human Laboratorymentioning
confidence: 99%
“…One possible explanation is that the pretreatment dose of d-amphetamine (i.e., 15 mg) was insufficient. It should be noted that previous studies that have demonstrated that the progressive-ratio procedure is sensitive to pharmacological pretreatment agents have been conducted with opioid drugs (e.g., Comer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%